(untitled) (ACTA MEDICA PERUANA, 2024)
We studled 2178 patlents who developed 2344 rheumatic diseases during a 5-year period (1982-1987) at the Hospital Regional Docente de Trujillo. We evaluated the frequency and characteristics in relation to place, time and person. Three groups of rheumatic diseases were predominant: nonarticular rheumatism, osteoarthritis and collagen tissue dlseases. The female to male ratio was 2: 1. Rheumatic diseases were found in ali age groups although half occurred in the 40 to 69 age group. About 80% carne from the provinces of Trujillo and were seen in the Services of Medicine, Rheumatology and Orthopedic Surgery. Fifly per cent of the diseases were diagnosed based only on clinical grounds. The proportlon of rheumatlc diseases represent 1.7% of the total of cases seen during the five years of the study.